Advancement Perforator Cheek Flap for Aesthetic One-Stage Reconstruction of Postoncological Extended Split-Thickness Defects of the Nasal Sidewall - Matteo Rossi; Arianna Milia; Marco Carmisciano; Salvatore D’Arpa; Adriana Cordova; Francesco Moschella (The Scientific World Journal)
Aesthetic reconstruction of soft tissue nasal sidewall loss has an important influence on the appearance of the nose. The unique character of this subunit and the complex relationships with a number of different facial or nasal subunits make the excision of large tumors difficult to manage. Numerous techniques are described in the literature, but a primary reconstruction with a final good result is not often possible. The authors develop an advancement cheek flap for an aesthetic one-stage reconstruction of postoncological extended nasal sidewall defects. Between January 2009 and July 2012, 16 patients (mean age, 63.3 yr) underwent excision of skin tumors of nasal sidewall and immediate reconstruction with an advancement cheek flap nourished by perforators from the transverse facial branch of the superficial temporal artery. The tumors were excised with 0.4–0.6 cm lateral margins and defects size ranged from 2.6 × 2.6 cm to 3.5 × 5 cm. Oncological radicality was obtained in all cases. The aesthetic results were excellent in all patients. No scar revision was needed. The authors’ advancement cheek flap can be considered the first choice for reconstruction of split-thickness defect of nasal sidewall larger than 2.5 cm because it reestablishes in one stage the nasal contour detail.